Co-existing concepts of management control: The containment of tensions due to the implementation of lean production. (June 2015) - Tillema, Sandra; van der Steen, Martijn
Abstract: There is substantial evidence that the implementation of lean production and similar innovations is not always successful. One of the explanations provided is that elements of traditional control systems may frustrate the transformation process. Although various studies have investigated the changes in control systems due to the implementation of lean production, only a few studies have explored the effects of the remaining traditional controls on lean implementations. This paper argues that lean production brings with it a new concept of control, which alters people's views of being in control. The new concept of control may co-exist with the traditional concept, but particularly at their interfaces, tensions may arise. Using case studies in four manufacturing companies in the Netherlands, this paper explores the various localised ways in which these companies dealt with such tensions to ensure that lean production continued. The paper concludes that lean transformations do not require a fundamental resolution of the problems that arise from inconsistent concepts of control, as long as companies have learned to cope with the localised tensions that may result from inconsistencies between such concepts.